The scholarship of transformation: A review of the Inaugural EuroSoTL Conference - Abrahamson, Earle (Teaching and Learning Inquiry, 2015)
A review of the Inaugural EuroSoTL Conference, Cork, Ireland, 7-9 June 2015.